2005
DOI: 10.1136/bmj.38434.629630.e0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of birth weight and adult body mass index in predicting risk of coronary heart disease and stroke in women

Abstract: Objectives To determine whether birth weight and adult body size interact to predict coronary heart disease in women, as has been observed for men. To determine whether birth weight and adult body size interact to predict risk of stroke. Design Longitudinal cohort study. Setting and participants 66 111 female nurses followed since 1976 who were born of singleton, term pregnancies and reported their birth weight in 1992. Main outcome measures 1504 events of coronary heart disease (myocardial infarction or sudde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
150
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(168 citation statements)
references
References 24 publications
14
150
3
1
Order By: Relevance
“…The association between SGA status and hypertriglyceridemia, hypertension, and impaired glucose metabolism is in concordance with previous studies (7,(26)(27)(28). However, waist circumference and HDL cholesterol levels as major components of the MetS were not related to SGA status in our study of overweight children.…”
Section: Discussionsupporting
confidence: 82%
“…The association between SGA status and hypertriglyceridemia, hypertension, and impaired glucose metabolism is in concordance with previous studies (7,(26)(27)(28). However, waist circumference and HDL cholesterol levels as major components of the MetS were not related to SGA status in our study of overweight children.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results are now evident in many countries including the United States, 24 Guatemala, Finland, China, and India. If the children are of low birth weight (LBW), then as shown in our Millennium analyses for the United Nations, 25 their likelihood of being underweight for age in the first few years of life is exceptionally high, because children would have to show accelerated growth from birth to be classified otherwise.…”
Section: Predicting the Risk Associated With Different Rates Of Childsupporting
confidence: 67%
“…There are few published studies on this subject, with contradictory results. One study found that each additional kilogram of birth weight was associated with a 11% decreased risk of stroke, with the exception of macrosomic infants [20]. In another cohort of women and men from Sweden, each kilogram increase in birth weight was associated with a 41% decreased risk of haemorrhagic stroke [21].…”
Section: Discussionmentioning
confidence: 99%